The Benefits and Challenges Associated with the Use of Drug Delivery Systems in Cancer Therapy - Cukierman, Edna (2010)
The use of Drug Delivery Systems as nanocarriers for chemotherapeutic agents can improve the pharmacological properties of drugs by altering drug pharmacokinetics and biodistribution. Among the many drug delivery systems available, both micelles and liposomes have gained the most attention in recent years due to their clinical success. There are several formulations of these nanocarrier systems in various stages of clinical trials, as well as currently clinically approved liposomal-based drugs. In this review, we discuss these drug carrier systems, as well as current efforts that are being made in order to further improve their delivery efficacy through the incorporation of targeting ligands. In addition, this review discusses aspects of drug resistance attributed to the remodeling of the extracellular matrix that occurs during tumor development and progression, as well as to the acidic, hypoxic, and glucose deprived tumor microenvironment. Finally, we address future prospective approaches to overcoming drug resistance by further modifications made to these drug delivery systems, as well as the possibility of coencapsulation/coadministration of various drugs aimed to surmount some of these microenvironmental-influenced obstacles for efficacious drug delivery in chemotherapy.